2017
DOI: 10.1021/acschembio.7b00748
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Color Palette of Fluorescent Copper Sensors through Systematic Heteroatom Substitution at Rhodol Cores

Abstract: Copper is an essential nutrient for sustaining life, and emerging data have expanded the roles of this metal in biology from its canonical functions as a static enzyme cofactor to dynamic functions as a transition metal signal. At the same time, loosely bound, labile copper pools can trigger oxidative stress and damaging events that are detrimental if misregulated. The signal/stress dichotomy of copper motivates the development of new chemical tools to study its spatial and temporal distributions in native bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 94 publications
(146 reference statements)
3
29
0
Order By: Relevance
“…In the range of pH 5–9, the probe itself remained almost non‐fluorescent; however, its three products formed by reaction with H 2 S, phosphatase, and both of them (Figure a) exhibited strong and stable fluorescence (Figure S11). Similar to the previously reported probe, the protonation of the piperazine group slightly decreased the green fluorescent signal from phosphatase at pH 5.…”
Section: Figuresupporting
confidence: 93%
“…In the range of pH 5–9, the probe itself remained almost non‐fluorescent; however, its three products formed by reaction with H 2 S, phosphatase, and both of them (Figure a) exhibited strong and stable fluorescence (Figure S11). Similar to the previously reported probe, the protonation of the piperazine group slightly decreased the green fluorescent signal from phosphatase at pH 5.…”
Section: Figuresupporting
confidence: 93%
“…S31 † and 8 ). 57 ATP7A is a P-type ATPase required for copper export. Loss of ATP7A function causes copper hyper-accumulation, 41 , 87 and previous ICP-MS studies have shown that the Atp7a –/– mouse embryonic fibroblast cells accumulate 6-fold more copper in the cytoplasm compared to isogenic wildtype cells.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of ATP7A function causes copper hyper-accumulation, 41 , 87 and previous ICP-MS studies have shown that the Atp7a –/– mouse embryonic fibroblast cells accumulate 6-fold more copper in the cytoplasm compared to isogenic wildtype cells. 57 Higher Cu levels would induce oxidative stress provided the excess Cu ions are bound to cellular ligands that promote redox cycling leading to Cu ion catalyzed ROS production. Therefore, we decided to check the level of ROS in the Atp7a –/– mouse embryonic fibroblast cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a different approach, Chang et al reported in 2018 the phospharhodol 32 (Figure ) and compared its properties with the carbon and silicon analogs . 32 possesses a thioether fragment linked to the 10‐position of the central backbone for the selective coupling with Cu + ions.…”
Section: Phosphorus Heteroarenes: the Originmentioning
confidence: 99%